BIS(2-(2-IZOPROPIL-5-METILFENOKSI)-2-OKSOETIL) OKSALAT SINTEZI - Choriyev , Azimjon; Abdushukurov Аnvar (Theoretical and experimental chemistry and modern problems of chemical technology, 2023)
2- Izoprophyl-5-methylphenole is used in many reactions, mainly in the synthesis of heterocyclic compounds, for example, pirimydines, calex- arene and ionic liquids. The purpose of the work is to carry out the reaction of O-chloracetylphenole with oxalate acid and to determine the physico-chemical and spectral properties of the reaction products.